Missense Variant of Endoplasmic Reticulum Region of WFS1 Gene Causes Autosomal Dominant Hearing Loss without Syndromic Phenotype. (4th March 2021) - Li, Jinying; Xu, Hongen; Sun, Jianfeng; Tian, Yongan; Liu, Danhua; Qin, Yaping; Liu, Huanfei; Li, Ruijun; Neng, Lingling; Deng, Xiaohua; Xue, Binbin; Yu, Changyun; et al.
Abstract : Objective . Genetic variants in the WFS1 gene can cause Wolfram syndrome (WS) or autosomal dominant nonsyndromic low-frequency hearing loss (HL). This study is aimed at investigating the molecular basis of HL in an affected Chinese family and the genotype-phenotype correlation of WFS1 variants. Methods . The clinical phenotype of the five-generation Chinese family was characterized using audiological examinations and pedigree analysis. Target exome sequencing of 129 known deafness genes and bioinformatics analysis were performed among six patients and four normal subjects to screen suspected pathogenic variants. We built a complete WFS1 protein model to assess the potential effects of the variant on protein structure. Results . A novel heterozygous pathogenic variant NM_006005.3 c.2020G>T (p.Gly674Trp) was identified in the WFS1 gene, located in the C-terminal domain of the wolframin protein. We further showed that HL-related WFS1 missense variants were mainly concentrated in the endoplasmic reticulum (ER) domain. In contrast, WS-related missense variants are randomly distributed throughout the protein. Conclusions . In this family, we identified a novel variant p.Gly674Trp of WFS1 as the primary pathogenic variant causing the low-frequency sensorineural HL, enriching the mutational spectrum of the WFS1 gene.